Future Directions in Cardiac Amyloidosis - Barry Trachtenberg (Methodist DeBakey Cardiovascular Journal)
Just a few years ago, cardiac amyloidosis (CA) was rarely diagnosed. With poor treatment options and delayed and infrequent diagnoses, most patients who were eventually recognized to have CA were referred for hospice care. Now, the availability of sponsored genetic testing, increased use of nuclear scintigraphy, and widespread recognition have contributed to an increasing number of patients being diagnosed with transthyretin amyloid cardiomyopathy (ATTR-CM). Concomitantly, with the increased recognition of concurrent conditions (eg, carpal tunnel syndrome, lumbar stenosis, and low-flow, low-gradient aortic stenosis), specialists such as orthopedic surgeons and structural cardiologists are increasingly involved in diagnosing ATTR-CM. Although the majority of patients are still being diagnosed either too late or having their diagnosis missed altogether, we have entered an exciting new era in the treatment of cardiac amyloidosis with improved diagnostic tools, disease recognition, and different therapeutic options for both ATTR and light-chain amyloidosis (AL). As a result, survival is improving, and we are no longer faced with a dualistic choice between hospice or organ transplant. The future goal is to develop anti-fibril therapies that will be safe and effective at removing deposited amyloid fibrils and restoring organs to their pre-amyloid state. For the millions of carriers of variant ATTR, enhanced testing followed by genetic editing may allow a cure even before patients develop clinical signs of the disease.